The Diversity for Restoration Tool is perceived as pivotal for strengthening decision-making on native tree species and seed sources among restoration stakeholders in Latin America - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
Diversity for Restoration (D4R) is a decision support tool that helps in species selection and seed sourcing for restoration using local site conditions and user-determined restoration objectives. D4R was first piloted for the Colombian tropical dry forest, but recently expanded to similar ecosystems in Peru, Ecuador and Burkina Faso, and soon Cameroon. Users of the tool report it is strengthening the seed selection decision-making process and is increasing awareness, knowledge transfer and data management among key stakeholders.